GLOBALIZACIÓN Y EMISIONES DE CO2 EN AMÉRICA LATINA: ¿IMPORTA EL NIVEL DE DEMOCRACIA? - Aguilera Ramón, Eddy Efraín (2021)
In recent years, a growing body of academic research has studied the behavior of CO2 emissions, as well as their determinants. However, most of the research focuses on the study of the traditional variables surrounding CO2 emissions. In this context, the objective of this research is to evaluate the causal relationship between globalization, democracy and CO2 emissions, for 18 Latin American countries classified by income, period 1980-2017. In this case, generalized least squares (GLS) regressions and panel data cointegration techniques are used. The results of the generalized least squares model show a positive effect of globalization on carbon emissions in Latin America, while democracy decreases emissions only in high-income countries (HICs). On the other hand, the cointegration results show that there is an equilibrium relationship between the variables, i.e. globalization, democracy, urbanization, inequality, corruption and CO2 emissions have a joint movement over the period analyzed. As for the causality results, they do not show solid evidence to assert strong causalities between the variables, although globalization allows for greater economic benefits, it is also contributing to increased environmental pollution in Latin America. Finally, Latin American economies should take advantage of globalization processes more efficiently, and incorporate more technology and productive processes that benefit environmental quality, as well as intensify environmental regulations with stricter policies.